Effects of in ovo Inoculation of Multi-Strain Lactobacilli on Cytokine Gene Expression and Antibody-Mediated Immune Responses in Chickens - Alizadeh, Mohammadali; Shojadoost, Bahram; Astill, Jake; Taha-Abdelaziz, Khaled; Karimi, Seyed Hossein; Bavananthasivam, Jegarubee; Kulkarni, Raveendra R.; Sharif, Shayan (Frontiers in Veterinary Science, 2020)
This study was conducted to investigate the effects of various doses of a multi-strain lactobacilli mixture (L. salivarius, L. reuteri, L. crispatus, and L. johnsonii) showed that the percentage of CD4 + and CD8 + splenocytes was not affected by treatments. In addition, no significant differences were observed for antibody titers against SRBC. However, lactobacilli treatment (P1, P2, and P3) was found to increase IgM titers on day 21 post-primary immunization compared to controls. Furthermore, in ovo injection of the highest dose of probiotics (1 × 10 7 , P3) increased serum IgG titers against KLH on day 7 post-primary immunization.In conclusion, this study demonstrated that that in ovo administration of 3 lactobacilli can improve antibody-mediated immune responses and differentially modulate cytokine expression in mucosal and systemic lymphoid tissues of chickens.